Comparative analysis of Sentinel-1 and PlanetScope imagery for flood mapping of Evros River, Greece - Theocharidis, Christos; Argyriou, Athanasios V.; Tsouni, Alexia; Kaskara, Mariza; Kontoes, Charalampos (My University, 2023)
The Evros region in Greece is prone to frequent floods, causing significant damage to infrastructure and communities. It is imperative to have an effective flood monitoring system in place to mitigate the risks associated with these natural disasters. Satellite remote sensing technology can provide vital information for monitoring and assessing the impact of such events. High-resolution satellite imagery and other remote sensing techniques can provide near real-time information on the floods' extent, severity, and dynamics, allowing for prompt and accurate responses of disaster management. This study integrated radar and optical imagery from Sentinel-1 and PlanetScope, respectively, to map the extent of a significant flood event along the Evros River from 12th of January to 01st of February 2021. Moreover, it exploits geomorphometric information through Digital Elevation Models (DEMs) to assess the flood risk zones. The region experienced the highest recorded rainfall in the last 50 years, making the event particularly noteworthy. More specifically, the Hellenic National Meteorological Service recorded an average monthly rainfall of 408 mm for January and 211 mm for the first ten days of February. The outcomes of this study highlight the benefits of interdisciplinary approaches and the synergy within optical and radar imagery, which can offer vital data to local authorities and stakeholders in decision making towards mitigation strategies and resilience in flood risk events.
Keywords: Sentinel-1; SAR; PlanetScope; Flood; Evros; Natural Hazard; Google Earth Engine; MNDWI